A New Virus Source Inference Model Based on Network Performance Estimation - Zhu, Hai Ting; Ding, Wei; Ni, Jun Hui (Applied Mechanics and Materials, 2013)
Combining network tomography, a new virus source inference model based on network performance is proposed. Both the topology information and real time network status are considered in our model. Performance metrics are introduced into rumor-centrality-based source detecting algorithm in an active inference way. By improving the process of setting up the spanning tree of infected topology we raise the virus source inference precision and reduce the time complexity of rumor-centrality-based algorithm from O(N2(|V|+|E|)) to O(N2). The simulation results show that our model achieves better estimation accuracy than the algorithm using rumor center as the estimator.